Complex approach in the process of physical education physical education of foreign students of technical specialties - Mavropulo O.S.; Demyanova L.M.; Zavodny N.A.; Chub S.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to increase the level of physical fitness of foreign students using an integrated approach in the educational process. The object of the study is the process of physical education of foreign students in higher education institution. The subject of the study is the physical training of foreign students of the faculty “Aircraft Engineering” within the discipline “Physical Culture and Sports”. Methods and structure of the study. The pedagogical research was organized in DSTU “Don State Technical University” Rostov-on-Don by the teaching staff of the department “Physical Culture and Sports and Recreational Technologies” within the framework of the educational process in the discipline “Physical Culture and Sports”. Results and conclusions. As a result of using an integrated approach to conducting physical education classes in the experimental group there was no significant difference in the level of physical fitness in relation to the control group. The problem of physical fitness of both foreign and Russian students, on our example, should be solved by increasing the number of practical classes in physical culture. Large breaks between classes can be the result of readaptation – return to the previous level of physical performance.